(untitled) (NPRC Journal of Multidisciplinary Research, 2025)
The study examined attitude of Islamic studies students’ towards learning of Arabic language in Asa Local Government, Kwara State, Nigeria. The study involved senior secondary school students of Islamic studies that offer Arabic Language in schools. In an attempt to do justice to this paper, the researcher used relevant materials such as text books, journals from Internet and other relevant materials in the course of this study. The finding of the study revealed that most Islamic studies students have positive attitude toward Arabic language and that Islamic studies students’ competence in learning Arabic language is relatively poor. It is concluded that teachers and students of Arabic Language should be giving adequate support to enhance to enhance effective teaching and learning of Arabic Language. Recommendations are provided, including improving teacher training, curriculum design, and creating a more supportive environment for Arabic language education. This paper underscores the need for collaborative efforts among stakeholders to enhance students’ motivation and performance in Arabic learning, ultimately bridging the gap between Islamic Studies and Arabic language acquisition.